Molecular Interactions of Renin with Chikusetsusaponin IV and Momordin IIc. (27th December 2019) - Zhang, Hai-Ling; Zhu, Gui-Lan; Chen, Xiao-Tian
Abstract : The paper dealt with the molecular mechanism for the binding sites and driving forces of renin with chikusetsusaponin IV and momordin IIc by means of molecular docking and free energy calculation based on the crystal structure. The result showed that renin and the saponins fit well. As shown by LigPlot + software analyzing the hydrogen bonding and hydrophobic effect between renin and the saponins, the amino acid residues such as Ser230, Tyr85, and Tyr201 form the hydrogen bonds, with S3 sp, S3, and S2′ being the active pockets. In addition, there are relatively strong hydrophobic interactions of renin with saponins in S3 sp, S3, S2, S1, S1′, and S2′, with Gly228, Val36, Ala229, Gln19, Met303, Gln135, Ser41, Ile137, Asp38, Arg82, and Tyr83 being the key amino acids. The dynamics reached equilibration after about 1000 ps simulation with average root-mean-square deviations of 0.222 nm and 0.217 nm. The molecular mechanics Poisson–Boltzmann surface area (MM-PBSA) yielded −1.10812 kcal/mol and −39.0587 kcal/mol total binding energy for the two complexes, respectively, which were primarily contributed by electrostatic and van der Waals interaction energies, and the binding was strongly unfavored by polar solvation energy, a further confirmation that momordin IIc has stronger hydrogen bonding and hydrophobic effect in the inhibition of renin than the chikusetsusaponin IV.